2003
DOI: 10.1021/np030067a
|View full text |Cite
|
Sign up to set email alerts
|

New Antimycobacterial and Antimalarial 8,9-Secokaurane Diterpenes from Croton kongensis

Abstract: Two new 8,9-secokaurane diterpenes, ent-8,9-seco-7alpha,11beta-diacetoxykaura-8(14),16-dien-9,15-dione (1) and ent-8,9-seco-8,14-epoxy-7alpha-hydroxy-11beta-acetoxy-16-kauren-9,15-dione (2), together with two known compounds, ent-8,9-seco-7alpha-hydroxy-11beta-acetoxykaura-8(14),16-dien-9,15-dione (3) and ent-7beta-hydroxy-15-oxokaur-16-en-18-yl acetate, were isolated from Croton kongensis. This is the first report on the presence of 8,9-secokauranes in the plant genus Croton. Diterpenes 1-3 exhibited antimyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 21 publications
0
34
0
2
Order By: Relevance
“…It is frequently used in folk medicine for dysmenorrhoea. 38 C. oblongifolius Roxb., popularly known as "chucka", is a middle-sized tree and grows in India and Thailand. The leaves are used as tonic, the flowers against flat worms, the fruits to treat dysmenorrhoea, the seeds as purgative, 39 the bark to treat dyspepsia and the roots to treat dysentery.…”
Section: Africamentioning
confidence: 99%
See 1 more Smart Citation
“…It is frequently used in folk medicine for dysmenorrhoea. 38 C. oblongifolius Roxb., popularly known as "chucka", is a middle-sized tree and grows in India and Thailand. The leaves are used as tonic, the flowers against flat worms, the fruits to treat dysmenorrhoea, the seeds as purgative, 39 the bark to treat dyspepsia and the roots to treat dysentery.…”
Section: Africamentioning
confidence: 99%
“…38 Plaunotol (5) has exhibited activity against twenty methicillin-resistant and fourteen methicillin-sensitive strains of Staphylococcus aureus. 187,188 The results suggested that plaunotol might be useful in the prevention of infection and skin care for patients with atopic dermatitis.…”
Section: Antibacterial Antifungal and Antiviralmentioning
confidence: 99%
“…(Euphorbiaceae) (Campos et al 2002;Almeida et al 2003;Rosa et al 2003), antimicrobial and the antimalarial effects Croton kongensis Gagnep. (Thongtan et al 2003), antinociceptive and anti-inflammatory properties of Croton malambo Karst. (Su arez et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the number of methylenes in the spacer from one to eight decreases MIC from 25 to 12.5 Pg/mL [18]. These results were unusual because 1, its bis-derivatives [18], and the aforementioned di-and triterpenoids of different structures [4,5,[8][9][10][11][12][13][14][15][16][17] are not nitrogenous organic compounds yet they exhibit antituberculosis activity at the level of the N-containing antituberculosis drug pyrazinamide (MIC = 12.5 Pg/mL) [19,20]. This is probably evidence that they have a different mechanism of M. tuberculosis growth inhibition.…”
mentioning
confidence: 99%
“…All other tuberculosis drugs [1] and agents undergoing preclinical and clinical trials [2,3] are products from organic syntheses. Nevertheless, over 50 metabolites of various structures that inhibit the growth of Mycobacterium tuberculosis in the range of minimum inhibiting concentrations (MIC) 60-3 Pg/mL have currently been isolated from natural plant sources [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Diterpenoids [4,5,[8][9][10][11][12][13] and triterpenoids [4,5,11,[14][15][16][17] are most widely represented among them.…”
mentioning
confidence: 99%